Trust negotiations: concepts, systems, and languages - Bertino, E.; Ferrari, E.; Squicciarini, A. (Computing in science & engineering, 2004)
Trust negotiation is a promising approach for establishing trust in open systems like the Internet, where sensitive interactions may often occur among entities with no prior knowledge of each other. In this article, the authors present a model for trust negotiation systems, and delineate the desiderata that ideal trust negotiation systems should satisfy. In defining trust negotiation requirements, they consider two different issues, policy language requirements and system requirements. They then survey the most interesting proposals that have been presented so far and evaluate them with respect to the identified requirements. Finally, they outline future research directions and identify the open issues that still have to be explored.